Chapter Professional Development Tutoring: Comparing Italian and International Models - Romano, Alessandra (Studies on Adult Learning and Education, 2018)
The paper presents the first outcomes of a comparative research of the incoming, on-going and outgoing practices of tutorship. The purposeful sample of universities extracted consisted of 18 Italian universities and 18 US universities. A tutorship concept in line with the transversal cross-curricular skills required for undergraduate and graduate students (Green Paper 2016, Dublin descriptors 2004) exceeds the vision of assistential tutorship and student tutoring practices, exercised by teachers and/or offered by services devoted to different types of intervention. The tutorship can be conceived as systemic and organizational action coherent in all phases with professionalising approach, starting from the earliest initiatives between school and university classrooms